2022
DOI: 10.1017/jns.2022.72
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced bioavailability and pharmacokinetics of a novel hybrid-hydrogel formulation of fisetin orally administered in healthy individuals: a randomised double-blinded comparative crossover study

Abstract: Fisetin, a polyphenol found in several fruits and vegetables, has shown potential health benefits in many pre-clinical studies for neuroprotection, cardioprotection, chemoprevention, diabetes, inflammation and oxidative stress. However, the clinical effectiveness of fisetin may be limited by its poor bioavailability when ingested. Using a novel green technology of Hybrid-FENUMAT™, a food-grade fisetin formulation (FF-20) was developed through encapsulation of fisetin micelles into fenugreek galactomannan (FG) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 42 publications
0
13
0
Order By: Relevance
“…The patient's compliance would be relatively high because it can be obtained in the daily diet. Nevertheless, its clinical application research is limited due to its poor water solubility, poor oral bioavailability, rapid metabolism, and degradation in the gastrointestinal tract after oral administration (Krishnakumar et al, 2022). Based on the poor bioavailability of fisetin after oral administration, frequent and high doses are expected to be more effective (Krishnakumar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The patient's compliance would be relatively high because it can be obtained in the daily diet. Nevertheless, its clinical application research is limited due to its poor water solubility, poor oral bioavailability, rapid metabolism, and degradation in the gastrointestinal tract after oral administration (Krishnakumar et al, 2022). Based on the poor bioavailability of fisetin after oral administration, frequent and high doses are expected to be more effective (Krishnakumar et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, its clinical application research is limited due to its poor water solubility, poor oral bioavailability, rapid metabolism, and degradation in the gastrointestinal tract after oral administration (Krishnakumar et al, 2022). Based on the poor bioavailability of fisetin after oral administration, frequent and high doses are expected to be more effective (Krishnakumar et al, 2022). Therefore, in the animal experiments, we used the intraperitoneal injection method instead of oral administration.…”
Section: Discussionmentioning
confidence: 99%
“…Hybrid-hydrogels have been identified as a promising approach for oral drug delivery systems since they can enhance the in vivo stability and release properties of drugs . High molecular weight, extensive hydration to stable softgel, mucoadhesive character, high emulsifying capacity, and amphiphilic nature to bind both oil and water make fenugreek galactomannan (FenuMAT) to behave like a cross-linked polymer for drug delivery. ,, The microstructure of FG allows the encapsulation of hydrophobic molecules in its conformationally directed hydrophobic pockets created in the swollen network. This is clear from the observed high encapsulation efficiency (>95%) of quercetin in FQ-35.…”
Section: Discussionmentioning
confidence: 99%
“…Such release properties of fenugreek galactomannan-based hydrogel formulations have already been reported for similar flavonoids, resveratrol, and fistein recently. 28 , 41 The hydrogel-quercetin system using β-lactoglobulin and sodium alginate has also been shown to exhibit good encapsulation efficacy and sustained release. 39 Similarly, Liu et al have reported quercetin encapsulation on whey protein microgels coated with lotus root amylopectin and its enhanced in vivo bioavailability, indicating the viability of hydrogel delivery systems.…”
Section: Discussionmentioning
confidence: 99%
“…Fisetin is considered a drug and nutritive supplement and is also recognized as a medical food, which stimulates more preclinical studies that could be translate into human clinical trials. One current clinical trial revealed important enhancement in anti-inflammatory markers when fisetin was injected into subjects with colorectal cancer [ 31 , 32 ]. A clinical study in stroke patients showed that fisetin was able to improve the treatment results, particularly in people with delayed onset-of-treatment [ 33 ].…”
Section: Introductionmentioning
confidence: 99%